The theory of monetary aggregation - Barnett, William A.; Serletis, Apostolos (Amsterdam ; New York : Elsevier, 2000)
In recent years, there has been renewed interest in index number and aggregation theory, since the two previously divergent fields have been successfully unified. The underlying aggregator functions which are weakly separable subfunctions of utility and production functions, are the building blocks of economic theory, and the derivation of index numbers based upon their ability to track those building blocks is now called the economic theory of index numbers. William Barnett, the coeditor of this volume, introduced modern economic index number theory into monetary economics. His merger of economic index number theory, with monetary theory was based upon the use of Diewert's approach to producing superlative nonparametric approximations to the theoretically exact aggregator functions.This book comprises a focussed and unified collection of Barnett's most important publications in this area. The papers in the book have been organized into logical sections, with unifying introductions and overviews. The result is a systematic development of the state-of-the-art in monetary and financial aggregation theory. The sections cover the origin of the user cost price of monetary services. Exact aggregation of monetary assets on the demand side for consumers and firms, and on the supply side for financial intermediaries, general equilibrium of all economic agents' demands and supplies, dynamic solution of the exact system, and extension to monetary aggregation under risk. The extension of index number theory to the case of risk is completely general, and can be applied to tracking any exact economic aggregator under risk. In all cases, the criterion used for evaluation is the tracking ability of the approximation to the exact aggregator function of economic theory.Many of the empirical and policy puzzles in monetary economics disappear when simple sum monetary aggregates are replaced by index numbers that are coherent with theory. Simple sum monetary aggregates became incoher
Understanding the new divisia monetary aggregates -- Economic monetary aggregates : an application of index number and aggregation theory -- Divisia indices -- Divisia monetary aggregates -- The optimal level of monetary aggregation -- New concepts of aggregated money / Paul Spindt -- A dispersion-dependency diagnostic test for aggregation error : with applications to monetary economics and income distribution / Apostolos Serletis -- Exact aggregation under risk -- Monitoring monetary aggregates under risk aversion / Piyu Yue -- CAPM risk adjustment / Mark Jensen -- Stochastic volatility in interest rates and nonlinearity in velocity / Haiyang Xu -- A reply to Julio J. Rotemberg -- Partition of M2+ as a joint product : commentary / Ge Zhou -- New indices of money supply and the flexible laurent demand system -- The new Divisia monetary aggregates / Paul A. Spindt -- Consumer theory and the demand for money / Apostolos Serletis -- The regulatory wedge between the demand-side and supply-side aggregation-theoretic monetary aggregates / Warren E. Weber -- Financial-firm production of monetary services : a generalized symmetric Barnett variable-profit-function approach / Jeong Ho Hahm -- Financial-firms' production and supply-side monetary aggregation under dynamic uncertainty / Ge Zhou -- The microeconomic theory of monetary aggregation -- Estimating policy-invariant deep parameters in the financial sector when risk and growth matter / Meenakshi Pasupathy -- Recent monetary policy and the Divisia monetary aggregates -- Which road leads to stable money demand? -- Perspective on the current state of macroeconomic theory -- The user cost of money -- Introduction to the St. Louis monetary services index project / Travis D. Nesmith.
Includes bibliographical references (p. 617-648) and indexes.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Index numbers (Economics); Monetary policy; Money supply; Business & Economics -- Inflation; Business & Economics -- Econometrics; Monetary economics; Finance